(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the cultural changes that took place in the southern regions of Uzbekistan in the years after the Second World War, including innovations in the field of education, the activities of cultural institutions, as well as the discriminatory policy of the Soviet government towards national culture, its consequences, the limitation of national values and the freedom of creativity of national intellectuals to conform to the communist ideology actions and its negative impact on national cultures are explained based on historical evidence and archival documents based on objective and comparative analysis methods.